2021
DOI: 10.3390/cells10010175
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Fatty Acids Modulate ER Lipid Composition and Metabolism in Breast Cancer Cells

Abstract: (1) Background: Lipid metabolism is a fundamental hallmark of all tumors, especially of breast cancer. Few studies describe the different lipid metabolisms and sensitivities to the microenvironment of breast cancer cell subtypes that influence the proliferation, aggressiveness, and success of therapy. This study describes the impact of lipid microenvironment on endoplasmic reticulum (ER) membrane and metabolic activity in two breast cancer cell lines with Luminal A and triple-negative breast cancer (TNBC) feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 44 publications
0
14
1
Order By: Relevance
“…As for breast cancer progression specifically, several studies show that fatty acid synthase (FASN) inhibition decreases proliferation and increases the chemosensitivity of many breast cancer cell lines as well as in experimental breast cancer models [22][23][24][25][26][27]. However, breast cancers are heterogenous with respect to fatty acid sensitivity [28] and metabolism, and, based on gene expression data, the less aggressive luminal A ER-positive breast cancer subtypes appear to rely on a balance between de novo lipogenesis and fatty acid oxidation as sources for both biomass and energy requirements, while basal-like, triple-negative subtypes may, to a larger extent, use exogenous fatty acids [29].…”
Section: Introductionmentioning
confidence: 99%
“…As for breast cancer progression specifically, several studies show that fatty acid synthase (FASN) inhibition decreases proliferation and increases the chemosensitivity of many breast cancer cell lines as well as in experimental breast cancer models [22][23][24][25][26][27]. However, breast cancers are heterogenous with respect to fatty acid sensitivity [28] and metabolism, and, based on gene expression data, the less aggressive luminal A ER-positive breast cancer subtypes appear to rely on a balance between de novo lipogenesis and fatty acid oxidation as sources for both biomass and energy requirements, while basal-like, triple-negative subtypes may, to a larger extent, use exogenous fatty acids [29].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, here we report that treatment with thapsigargin or tunicamycin does not significantly alter tubular SER polygon area or the proportion of dense RER within U-2 OS cells. Lipid availability has been linked to ER morphology [25] and treatment with the saturated free fatty acid palmitate induces ER expansion and stress in several cell types [32,[60][61][62][63]. Here we show that treatment with a low concentration of palmitic acid increases the area of SER polygons.…”
Section: Discussionmentioning
confidence: 50%
“… 59 Moreover, a recent study showed that luminal A and TNBC cell lines have different lipid phenotypes, suggesting that different lipid metabolism might discriminate breast cancer subclasses. 60 This might explain the discriminative feature of ACBD4 as a luminal associated gene in the BP gene signature.…”
Section: Resultsmentioning
confidence: 99%